Conservation Ethics of Plants in India - Dashora, Kavya; Bhardwaj, Meenakshi; Gupta, Anjali (Indian Forester, 2010)
The cult of worshipping plants as a blessing from God on earth has its roots deep in the history of human civilization. Plants were considered as a solemn symbol that protected and defended man in various ways. Over the centuries, possibly, the world's first recorded conservation measures were enacted in India by emperor Ashoka, the Great. Later on, the agricultural practices and the other daily chores of primitive man provided definite clues for the significant tradition conservation. However, with the human population increasing manifolds, the production pressure on the land has also increased simultaneously. The enhanced rate of production, exploitation and exhaustion has left us with unabated devastation of resources. Whatever has remained is due to the socio cultural and religious traditions. Keeping this in mind, the present article is an attempt to have a glimpse into the ethnic, social and religious practices adopted in various parts of the country leading to the conservation of natural wealth.